2021
DOI: 10.1093/trstmh/trab123
|View full text |Cite
|
Sign up to set email alerts
|

Rabies and the pandemic: lessons for One Health

Abstract: This article examines the impact of coronavirus disease 2019 (COVID-19) on dog-mediated rabies, a neglected tropical disease that remains endemic in >65 countries. A globally agreed strategy for rabies elimination is underpinned by a One Health approach, coordinating human and animal health sectors and engaging communities. We present data on the scale and nature of COVID-19 disruption to rabies control programmes and the wider learning for One Health implementation. We argue that the global shift in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…Rabies control is a model for One Health implementation, as its proven methodologies demonstrate the effectiveness of collaboration at the human-animal interface, including at community and municipal level. However, the pandemic has also set back many countries' efforts toward rabies elimination ( 4 ).…”
Section: Rabies and One Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabies control is a model for One Health implementation, as its proven methodologies demonstrate the effectiveness of collaboration at the human-animal interface, including at community and municipal level. However, the pandemic has also set back many countries' efforts toward rabies elimination ( 4 ).…”
Section: Rabies and One Healthmentioning
confidence: 99%
“…A recent survey found that rabies workforce capacity and financial resources were redirected toward COVID-19, movement restrictions limited access to healthcare facilities, and overwhelmed health systems had less capacity to treat cases of rabies exposure ( 4 ). Community outreach, including rabies prevention programs in schools, were suspended and the disruption of medical supply chains resulted in restricted PEP access for exposed individuals.…”
Section: Rabies and One Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 pandemic has disrupted many essential health services including strategies for rabies elimination ( 32 ) with funding for non-COVID-19 disease projects redirected to control of COVID-19. These has disrupted mass dog vaccination, provision of PEP and community awareness activities ( 33 ). Funding rabies elimination programs will require local ownership and financing from governments in endemic countries such as Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has disrupted the lives and economies of most countries all over the world, whether directly or indirectly ( 29 ). As public health professionals are diverted to working on the pandemic, it has disrupted vaccination campaigns in countries ( 30 ), including rabies vaccination, and field training.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%